Surveillance of Brucella in Red Meat Sold at Retail Outlets - Almashhadany , Dhary Alewy (Trends in Sciences, 2021)
Brucellosis in the Middle East is endemic and is associated with health burdens and economic losses for animals and humans. Transmission of Brucella from animal hosts to humans is prevalent in endemic areas, especially developing countries. This study aimed at screening for the brucellae in different fresh red meat sold in retail markets in Erbil city, Iraq. A total of 410 samples were collected between July and December 2019 and analyzed by serological and bacteriological tests for Brucella spp. by Rose Bengal Test (RBT), ELISA, and traditional bacterial culture. The prevalence of Brucella was 9.3, 7.8 and 7.1 % by RBT, ELISA, and bacteriological analysis, respectively. Both B. abortus and B. melitensis were detected in 3.17 % and 3.90 % of collected samples, respectively. In terms of seasonal variation, autumn was found to be associated with a decrease in seroprevalence. RBT was found to be suitable for ruling out the disease, but its positive results should be confirmed. The overall prevalence of Brucella in meat or the source livestock is alarming and requires considerable actions to prevent the transmission of brucellae to humans. HIGHLIGHTS The prevalence of Brucella in meat samples sold in Erbil is 7 - 10 % Rose Bengal Test is convenient ruling out the disease in animals but its positive results should be confirmed The seasonality of Brucella in livestock of Erbil showed slight decrease during the autumn season GRAPHICAL ABSTRACT